Environment & pollution, an ecological approach - Ambasht, R. S.; Ambasht, P. K. (Varanasi, India : Students' Friends, 1992)
Textbook.
"The book ... has been thoroughly revised ... In the second edition two new chapters have been added on Fundamental Aspects of Air Pollution (IX) and on Environmental Protection Efforts in India (XXI)"--Pref.
Includes bibliographical references (p. [290]-302) and index.
Keywords: Pollution; Ecology